PROSPECTS FOR THE DEVELOPMENT OF REINFORCED CONCRETE STRUCTURES IN UZBEKISTAN - Akhmedov Islombek; S.Kholmirzayev; Umarov Isroil; F.Dadaxanov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This scientific article shows the role, importance of reinforced concrete structures in construction methods of increasing economic efficiency in the process of applying reinforced concrete structures. Work on the development of reinforced concrete structures in developed countries of the world and the prospects for the development of reinforced concrete structures in the Republic of Uzbekistan are covered.